Motivasi Munfik Terhadap Minat Berinfak Melalui Program Penitipan Kaleng Infak Baznas Kabupaten Sorong - Nafaizatul i Khasanat; Fatma Sari; Karfin Karfin (At-Thariqah: Jurnal Ekonomi, 2022)
The main problem of this research is how the motivation of hypocrites affects the interest in giving in the infaq can care program BAZNAS Sorong district. This study aims:1) To find out what is the motivation for the interest of hypocrites in giving infaq in the infaq can program of BAZNAS Sorong Regency. 2) To find out whether there are opportunities and challenges from the implementation of the BAZNAS infaq program in Sorong Regency. The approach used is a quantitative research approach whose results are calculated using analysis techniques and classical assumption tests, simple linear regression and hypothesis testing with the help of SPSS V.28, the type of research used is descriptive correlation research. The sample used was 34 respondents who were selected through the census sample technique or saturated sample. Based on the results of the study, it showed that motivation had a significant positive effect on the interest in donating in the infaq can program of BAZNAS, Sorong Regency. The magnitude of the contribution of the independent variable or motivation is 0.116 or 11.6%. The implication of this research is for BAZNAS Sorong Regency to continue to pay attention to things that affect the motivation to donate in the ongoing BAZNAS infaq can program.